Looking Beyond Averages in the Trade and Poverty Debate - Ravallion, Martin (World Bank, Washington, D.C., 2013)
There has been much debate about how much poor people in developing countries gain from trade openness, as one aspect of "globalization." The author views the issue through both "macro" and "micro" empirical lenses. The macro lens uses cross-country comparisons and aggregate time series data. The micro lens uses household-level data combined with structural modeling of the impacts of specific trade reforms. The author presents case studies for China and Morocco. Both the macro and micro approaches cast doubt on some wide generalizations from both sides of the globalization debate. Additionally the micro lens indicates considerable heterogeneity in the welfare impacts of trade openness, with both gainers and losers among the poor. The author identifies a number of covariates of the individual gains. The results point to the importance of combining trade reforms with well-designed social protection policies.